George Eugene Dodge, A Digest of the Laws and Ordinances of the City of Little Rock, with the Constitution of State of Arkansas, General Incorporation Laws, and All Acts of the General Assembly Relating to the City 230-31 (1871) - (:unkn) unknown (My University, 1871)
Prohibited carrying of a pistol, revolver, Bowie knife, dirk, rifle, shot gun, slungshot, colt, or metal knuckles while engaged in a breach of the peace. Punishable by a fine of $25-500.
Keywords: CARRY - INTENT TO COMMIT CRIME